Learning Problems of Children with Special Needs in Kindergarten - Hadirah Hadirah; Moh Syafik (Department of Special Education, 2018)
This study is mainly purposed to investigate the teaching method and approach used by the teachers in teaching special needs students in TK Al-Faizin, the learning problems (barriers) faced by teachers and the ways to solve these learning problems (barriers) of special needs student in TK Al-Faizin. This research is a descriptive qualitative research using observation, interview, and documentation to collect the data. 3 steps of analyzing the data involves data reduction, data display, and conclusion by Miles and Huberman. The results revealed that the teacher used the model of group learning with safety activities and various learning methods based on theme-based approach. The problems (barriers) faced by teachers included value barriers, power barriers, practical barriers, and psychological barriers. To solve the problems, teachers adapt the curriculum, collaborate with the parent, improve their teaching competence through independent learning, share with their peer teachers, and hold a parenting program once a month.